Bank efficiency and share prices in China: empirical evidence from a three-stage banking model. (9th November 2009) - Sufian, Fadzlan; Majid, Muhamed Zulkhibri Abdul
This paper examines the relationship between the efficiency of China banks and its share price performance. Our analysis consists of three parts. First, we calculate the annual share price returns of the banks for each year between 1997 and 2006. Then we employ the data envelopment analysis (DEA) window analysis method to estimate the efficiency of each bank. Finally, we regress the annual share price returns on the change in efficiency, while controlling for other bank specific traits. The empirical findings suggest that large Chinese banks have exhibited higher technical and pure technical efficiency levels compared to their small and medium sized bank counterparts, while the medium sized banks have exhibited higher scale efficiency. The relationship between Chinese banks' efficiency and share price performance suggest that bank efficiency estimates derived from the DEA window analysis method contributes significant information towards share price returns beyond that provided by financial information.